Response of broadleaved evergreen Mediterranean forest vegetation to fire disturbance during the Holocene: insights from the peri-Adriatic region (Journal of Biogeography, 2009)
Aim To test whether fire contributed to the expansion and compositional change of evergreen forests in the Mediterranean region during the Holocene. Location The peri-Adriatic region, encompassing the Italian peninsula, Sicily and the western and southern Balkans between latitudes 46° and 37° N. Methods New high-resolution pollen and microscopic charcoal data from Lago dell’Accesa (Tuscany, Italy) were used to estimate the response of the evergreen oak, Quercus ilex L., to fire during its expansion phase at 8500 cal. yr bp. The data were compared with the pollen and charcoal series from other Mediterranean sites (Lago di Massaciuccoli in Tuscany, Malo Jezero in Croatia, Biviere di Gela in Sicily) and analysed using numerical techniques (redundancy analysis, detrended canonical correspondence analysis) to identify long-term fire–vegetation linkages and the degree of compositional change. Results Microscopic charcoal and pollen of evergreen oaks were negatively correlated during the period of quasi-natural fire regime (Mesolithic, 10,000–8000 cal. yr bp). In addition, there was no such positive correlation during periods when the fire regime was potentially more influenced by people (Neolithic–Bronze Age, 8000–3000 cal. yr bp). Compared with inland sites, coastal sites that are currently located at a distinct ecotone showed more compositional change. Main conclusions The analyses suggest that climatic change, without an additional effect of fire regimes, favoured the expansion and compositional change of evergreen forests across the peri-Adriatic region. Strikingly different patterns occurred along a north–south gradient. In the north (Tuscany and Croatia, meso-Mediterranean belt), Q. ilex replaced deciduous forests when conditions became drier; in the south (Sicily, thermo-Mediterranean belt) the species replaced maquis or steppe vegetation when climatic conditions became moister. We conclude that the projected increase in fire activity may lead to the loss of most of the remaining relict forests of Q. ilex in southern Europe.